Quality of Life of Heart Transplant Patients During the Covid-19 Pandemic - Ferreira, Jhienniffer; Poltronieri, Nadja Van Geen (Brazilian Journal of Transplantation, 2022)
The objective of this study was to evaluate the quality of life of heart transplant recipients during the pandemic of COVID-19 through a cross- sectional, descriptive and quantitative study. Individuals under treatment in a tertiary cardiology hospital in the city of São Paulo (SP) were included.The sample was 40 transplanted individuals with a time frame of more than one year and age over 18 years. The instrument was the World Health Organization Quality of Life questionnaire (WHOQOL-BREF) from October 2021 to January 2022. After data collection, a compilation was made with descriptive analysis of the variables and calculation of the instrument, obtaining as a final result the calculation of the mean and standard deviation. The results highlighted the importanceof improvements in several facets of each domain and public issues related to public transportation and daily life safety. It was possible to observe numerous difficulties in relation to the availability and ease of access in various sectors, a situation that also led to changes in the perception and quality of health as a whole, with sudden changes in the population’s daily lives. The study was satisfactory, making it possible to evaluate points of improvement in the quality of life of heart transplant recipients during the pandemic of COVID-19.